2017
DOI: 10.1371/journal.pone.0172997
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1 identified in Avian Pathogenic Escherichia coli (APEC)

Abstract: Antimicrobial resistance associated with colistin has emerged as a significant concern worldwide threatening the use of one of the most important antimicrobials for treating human disease.Here, we examined a collection (n = 980) of Avian Pathogenic Escherichia coli (APEC) isolated from poultry with colibacillosis from the US and internationally for the presence of mcr-1 and mcr-2, genes known to encode colistin resistance. Included in the analysis was an additional set of avian fecal E. coli (AFEC) (n = 220) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 60 publications
4
76
0
Order By: Relevance
“…In Egypt, only one E. coli from a cow was identified to carry mcr-1 (Khalifa et al, 2016). In another study, three avianpathogenic E. coli isolates from chickens in Egypt were also reported to be mcr-1 positive (Lima Barbieri et al, 2017).…”
Section: Livestockmentioning
confidence: 98%
“…In Egypt, only one E. coli from a cow was identified to carry mcr-1 (Khalifa et al, 2016). In another study, three avianpathogenic E. coli isolates from chickens in Egypt were also reported to be mcr-1 positive (Lima Barbieri et al, 2017).…”
Section: Livestockmentioning
confidence: 98%
“…However, due to the possibility of both fitness cost of some bacteria by expressing mcr-1 (Yang et al, 2017;Nang et al, 2018) and the incomplete evolution of mcr-1, the mcr-1 only presented in E. coli in sporadical cases for nearly two decades. Following the huge amounts of colistin used in animals (Kempf et al, 2016), the mcr-1 gene in bacteria started to increase in several continents and countries in the beginning of the 21th century, such as China in 2004 (Shen et al, 2016), Japan in 2007 (Kusumoto et al, 2016), France in 2005 (Haenni et al, 2016), Egypt in 2010 (Lima Barbieri et al, 2017), and Brazil in 2012 (Fernandes et al, 2016). With continuous antimicrobial pressure, mcr-1 has been evolved to have negligible fitness cost or even advantage to its host (Zhang et al, 2017;Wu et al, 2018).…”
Section: Prevalence Evolution and Spread Of Mcr Genesmentioning
confidence: 99%
“…For poultry, there are no relevant indications other than colibacillosis given that for Salmonella infections antimicrobial use is prohibited (Löhren et al, 2009). Indeed, several publications mention that the main indication of colistin in poultry is the treatment of mild colibacillosis (Kempf et al, 2013;Catry et al, 2015;Barbieri et al, 2017). Nonetheless, the bioavailability of colistin following oral administration in poultry has proven to be very low since it is not well absorbed from the GI tract (e.g.…”
Section: Use Of Colistin In Veterinary Medicine and In Poultry Producmentioning
confidence: 99%
“…Limited studies from Africa showed a low prevalence of clinical and commensal E. coli in South African and Tunisian broilers, respectively (Table 1). Furthermore, the retrospective investigation of Barbieri et al (2017) discovered low prevalence of mcr-1 in clinical E. coli and absence of the gene in their commensal counterparts, in an international collection of poultry-derived isolates.…”
Section: Commensal and Pathogenic E Colimentioning
confidence: 99%